2021
DOI: 10.1155/2021/6646017
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Computer Simulation on Students’ Performance in Teaching and Learning Physics: Are There Any Gender and Area Gaps?

Abstract: The aim of this study is to determine the effect of using computer simulation on students’ performance in teaching and learning physical science, particularly the electrical Ohm’s law. A sample of 182 students classified into two groups–experimental (92) and control (90)–from two middle schools in Meknes city (one in the rural area and the other urban area) was the subject of a pretest and posttest evaluation. The outcomes of the administered test to both groups of students, control and experimental, were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
4
11
0
4
Order By: Relevance
“…These findings seem to hint that the affordances of the PhETs promoted learners' conceptual change as well as conceptual development of the subject matter-an indication of the extent to which the PhETs facilitated understanding of the physics concepts taught. This explanation is consistent with findings from previous studies (Barak & Dori, 2005;Bell & Smetana, 2008;Dega et al, 2013;Jimoyiannis & Kosmis, 2001;Hannel & Cuevas, 2018;El Kharki et al, 2020;Ouahi et al, 2021;Pucholt, 2021;Trundle & Bell, 2005). Specifically, findings in these studies situate computer simulations as useful tools for the enhancement of students' conceptual understanding of concepts in physics.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings seem to hint that the affordances of the PhETs promoted learners' conceptual change as well as conceptual development of the subject matter-an indication of the extent to which the PhETs facilitated understanding of the physics concepts taught. This explanation is consistent with findings from previous studies (Barak & Dori, 2005;Bell & Smetana, 2008;Dega et al, 2013;Jimoyiannis & Kosmis, 2001;Hannel & Cuevas, 2018;El Kharki et al, 2020;Ouahi et al, 2021;Pucholt, 2021;Trundle & Bell, 2005). Specifically, findings in these studies situate computer simulations as useful tools for the enhancement of students' conceptual understanding of concepts in physics.…”
Section: Discussionsupporting
confidence: 93%
“…Findings revealed that additional instructional support was key to improvements observed in students' understanding of the concepts investigated. Other benefits of computer simulations in relation to physics learning include "improving the teaching/learning process based on conceptual understanding" (El Kharki et al, 2020, p. 131;Pucholt, 2021), promoting interactivity in the physics classroom , enhancing students' performance in learning physics (Ouahi et al, 2021) and affording students the space to explore a wide range of topics in physics through its multiple representation feature (Fan et al, 2018;Nadiradze et al, 2020;Podolefsky et al, 2010). These seem to reflect the potentials of PhET simulations, in that, they are designed to provide interactive platforms that engage students to learn through exploration and discovery with the goal to help students to connect real-life phenomena to the underlying subject matter in a particular science (Finkelstein et al, 2006;Wieman et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results indicated that students in the experimental group had significantly improved visual thinking following the intervention and were able to perceive and comprehend the problem situation considerably more easily than students in the control group. Our findings support previous research [42][43][44][45] that suggests using simulations can assist science students in developing visual thinking skills such as observation, measurement, prediction, and interpretation of outcomes.…”
Section: On Improving Student's Visual Thinkingsupporting
confidence: 91%
“…Furthermore, the results confirmed the benefits of computer simulations by promoting interactivity in the physics classroom [52], improving students' performance when learning physics [53], and providing students with the opportunity to explore a broad range of physics topic areas via the multiple representation feature [45,54,55].…”
Section: On Improving Student's Visual Thinkingsupporting
confidence: 54%
“…Some respondents of the study also expressed those interactive simulations is one of the strategies used in Science teaching. In addition, according to Ouahi (2021), the proliferation of data and the growth in the breadth and depth of human understanding need the use of a variety of approaches to educating future scientists. It has also seemed necessary to establish a mode of instruction that will streamline and facilitate the learning process for the students.…”
Section: Mainmentioning
confidence: 99%